PENGARUH PENGALAMAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA GURU DI PODOK PESANTREN - Pancagaluh Ratnasih (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
Moral degladation is evidence of educational failure. Therefore, Islamic education is present as a solution. As an effort to organize quality education it is necessary to improve teacher performance. This study was conducted to determine the effect of work experience and job satisfaction on teacher performance in the Al-Hidayah Islamic Boarding School in Lebak-Banten. The research method used is a quantitative method with descriptive and inferential explanations. The population in this study was 50 teachers in Al-Hidayah Islamic Boarding School, Lebak - Banten, with 50 samples using saturated samples. The analytical method used is multiple linear regression analysis using SPSS 22 statistical tools. The results showed that experience and satisfaction had effect on teacher performance. This finding confirms that teacher performance does not increase by itself. But there are many efforts behind it, including experience and satisfaction